Differentiated Lithium Salt Design for Multilayered PEO Electrolyte Enables a High‐Voltage Solid‐State Lithium Metal Battery - Wang, Chen (Adv Sci (Weinh), 2019)
Low ionic conductivity at room temperature and limited electrochemical window of poly(ethylene oxide) (PEO) are the bottlenecks restricting its further application in high‐energy density lithium metal battery. Herein, a differentiated salt designed multilayered PEO‐based solid polymer electrolyte (DSM‐SPE) is exploited to achieve excellent electrochemical performance toward both the high‐voltage LiCoO(2) cathode and the lithium metal anode. The LiCoO(2)/Li metal battery with DSM‐SPE displays a capacity retention of 83.3% after 100 cycles at 60 °C with challenging voltage range of 2.5 to 4.3 V, which is the best cycling performance for high‐voltage (≥4.3 V) LiCoO(2)/Li metal battery with PEO‐based electrolytes up to now. Moreover, the Li/Li symmetrical cells present stable and low polarization plating/stripping behavior (less than 80 mV over 600 h) at current density of 0.25 mA cm(−2) (0.25 mAh cm(−2)). Even under a high‐area capacity of 2 mAh cm(−2), the profiles still maintain stable. The pouch cell with DSM‐SPE exhibits no volume expansion, voltage decline, ignition or explosion after being impaled and cut at a fully charged state, proving the excellent safety characteristic of the DSM‐SPE‐based lithium metal battery.